2021
DOI: 10.3758/s13420-021-00488-z
|View full text |Cite
|
Sign up to set email alerts
|

Context, attention, and the switch between habit and goal-direction in behavior

Abstract: This article reviews recent findings from the author’s laboratory that may provide new insights into how habits are made and broken. Habits are extensively practiced behaviors that are automatically evoked by antecedent cues and performed without their goal (or reinforcer) “in mind.” Goal-directed actions, in contrast, are instrumental behaviors that are performed because their goal is remembered and valued. New results suggest that actions may transition to habit after extended practice when conditions encour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 96 publications
4
78
0
Order By: Relevance
“…For example, a recent study by Dormal and colleagues (Dormal et al, 2020 ) suggested that combining the GNG paradigm with transcranial direct-current stimulation may be a promising way to improve IC in BD as it was shown to promote attention-related brain activity. In addition, Bouton ( 2021 ) recently reviewed a number of animal studies which demonstrate that a habit can be returned to a goal-directed action, for example by a context switch or pharmacological interventions. However, there is at present a scarcity of experimental studies in humans to enhance our understanding how habit behavior in addiction can be addressed apart from increasing response inhibition or extinguishing cue-conditioned responses, both of which are of limited effectiveness (Jones et al, 2016 ; Mellentin et al, 2017 ).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…For example, a recent study by Dormal and colleagues (Dormal et al, 2020 ) suggested that combining the GNG paradigm with transcranial direct-current stimulation may be a promising way to improve IC in BD as it was shown to promote attention-related brain activity. In addition, Bouton ( 2021 ) recently reviewed a number of animal studies which demonstrate that a habit can be returned to a goal-directed action, for example by a context switch or pharmacological interventions. However, there is at present a scarcity of experimental studies in humans to enhance our understanding how habit behavior in addiction can be addressed apart from increasing response inhibition or extinguishing cue-conditioned responses, both of which are of limited effectiveness (Jones et al, 2016 ; Mellentin et al, 2017 ).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…In an instrumental learning setting, reinforced lever pressing not only leads to instrumental action-outcome and stimulusresponse associations, but also pavlovian associations between the reinforcer and discrete or contextual stimuli (Milton and Everitt, 2010). While action-outcome and stimulus-response associations may be mutually inhibitory, thereby allowing only one of the two to control behavior (Bouton, 2021), instrumental and pavlovian associations may be active in parallel. This leads to the question of whether two independent associations can both be destabilized in parallel by the same reactivation session.…”
Section: Introductionmentioning
confidence: 99%
“…How automatic sequences of actions are learned and what factors contribute to their development is not well understood. While the study of human behaviors both in health (Keller et al, 2021; Luque et al, 2020; Smith and Graybiel, 2016) and disease (Burguière et al, 2015; Byrne et al, 2021; O’Tousa and Grahame, 2014) provides useful insights into these mechanisms, many investigations of the molecular and circuit underpinnings of automatic behaviors are currently performed in rodents (Bouton, 2021; Burguière et al, 2015; Faure et al, 2005; Gremel and Costa, 2013; Lerner, 2020; Renteria et al, 2018; Wassum et al, 2009) due to the availability of genetic and optogenetic tools. Understanding the features of training paradigms that effectively or ineffectively promote the emergence of reproducible behavioral sequences is therefore necessary to take full advantage of the tools only accessible to rodent research, and to identify the circuits, cell types and molecular mechanisms that control sequences of stereotypical actions.…”
Section: Introductionmentioning
confidence: 99%